THE EFFECT OF ORGANIZATIONAL CULTURE AND INTERNAL COMMUNICATION ON TEACHER PERFORMANCE AT ISLAMIC BOARDING SCHOOLS THROUGHOUT THE LAWANG WETAN SUBDISTRICT - Haidarul Amjad; Zainal Berlian; Nurlaila Nurlaila (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the influence of organizational culture and internal communication on teacher performance at Islamic boarding schools in Lawang Wetan District. The study employed a quantitative approach using an ex post facto method and a verificative research design. The research population consisted of all teachers at Ash-Shiddiqiyah Islamic Boarding School and Riyadhul Iman Islamic Boarding School in Lawang Wetan District. Data were collected through the distribution of questionnaires to respondents. The data analysis technique used was multiple linear regression analysis with the assistance of the SPSS program. The results of the study indicate that partially, organizational culture does not have a significant effect on teacher performance. This is shown by the calculated t-value of 1.535, which is smaller than the t-table value of 1.994, with a significance level of 0.130 > 0.05. However, organizational culture still demonstrates a positive direction of influence on teacher performance. Meanwhile, internal communication has a positive and significant effect on teacher performance, with a calculated t-value of 4.275, which is greater than the t-table value of 1.994, and a significance value of 0.000 < 0.05. Simultaneously, organizational culture and internal communication significantly influence teacher performance, as indicated by the calculated F-value of 17.534, which is greater than the F-table value of 3.13, with a significance value of 0.000 < 0.05. The findings of this study reveal that internal communication is the dominant factor in improving teacher performance within the Islamic boarding school environment. Therefore, it is necessary to strengthen the internal communication system and develop a more adaptive organizational culture in order to improve the quality of teacher performance.